Temporomandibular joint (TMJ) disorders as first clinical manifestations in external auditory canal cholesteatoma. A case report. (February 2022) - Salimi, Fatemeh; Motter, Dema; Salimi, Zahra
Abstract: Introduction and importance: Cholesteatoma is a common occurrence in the middle ear, whereas cholesteatoma of the external auditory canal (EAC) is a rare condition. We report an unusual presentation of the cholesteatoma in the EAC. Case presentation: We report a case of a 67-year-old male presented to the ENT casualty with a longstanding history of left sided squeaky type sound, aggravated whenever he talks or eats. He subsequently had a Computed Tomography (CT) scan of the left petrous bone which identified a left-sided EAC cholesteatoma. Clinical symptoms of EAC cholesteatoma are non-specific, and hence we recommend considering cholesteatoma when patients present with abnormal EAC symptoms and intact tympanic membrane. Clinical discussion: His cranial nerves examination was normal, and the tympanic membrane was intact. His blood count and infective marker were normal. The CT scan of the brain showed a lesion in the left external auditory canal close to the tympanic membrane. The lesion was in contact with the anterior inferior canal wall which had features suggesting bony erosion. Gas bubble seen in the posterior part of the TMJ was in relation to bony erosion of the EAC. Conclusion: The cholesteatoma of the EAC is very rare. CT scan can provide detailed information about the extent of external ear canal cholesteatoma, which can be used to identify complications of the disease, in addition to differentiating the external ear canal from the middle ear cholesteatoma. Early recognition of cholesteatoma and prompt treatment is essential to prevent catastrophic complications. Highlights: A cholesteatoma originating in the external auditory canal is a rare finding. Cholesteatoma can present with atypic symptoms such as temporomandibular joint disorders.